lncRNA MEG8 Upregulates miR-770-5p Through Methylation and Promotes Cell Apoptosis in Diabetic Nephropathy - Zhang J (Dove Medical Press, 2020)
Jinmei Zhang,1 Liwen Song,2 Yanjuan Ma,3 Yan Yin,1 Xinqi Liu,1 Xinyu Luo,1 Jiali Sun,1 Liqin Wang1 1Department of Endocrinology, Weifang Hospital of Traditional Chinese Medicine, Weifang, Shandong Province 261000, People’s Republic of China; 2Department of Endocrinology, Weifang People’s Hospital, Weifang, Shandong Province 261000, People’s Republic of China; 3Department of Endocrinology, Sunshine Fusion Hospital, Sunshine, Shandong Province 261061, People’s Republic of ChinaCorrespondence: Liwen SongDepartment of Endocrinology, Weifang People’s Hospital, Weifang City, Shandong Province 261000, People’s Republic of ChinaTel +86 536-963360Email zjmmjmdr@126.comBackground: It has been reported that lncRNA MEG8 can be induced by glucose in mice model of kidney injury, indicating its role in diabetic nephropathy (DN). This study was carried out to explore the role of MEG8 in DN.Materials and Methods: The expression of MEG8 and miR-770-5p in plasma samples from DN patients (n = 66), diabetic patients (DM patients with no complications, n = 66) and healthy controls (n = 66) was detected by RT-qPCR. The interaction between MEG8 and miR-770-5p in podocyte cells was evaluated by transient transfections. Cell apoptosis under high-glucose treatment was detected by cell apoptosis assay.Results: MEG8 and miR-770-5p were upregulated in plasma of DM patients and were further upregulated in DN patients. MEG8 was positively correlated with miR-770-5p. In podocyte cells, high-glucose treatment resulted in increased expression levels of MEG8 and miR-770-5p. In podocyte cells, overexpression of MEG8 resulted in upregulated expression of miR-770-5p and decreased methylation of the miR-770-5p gene. Cell apoptosis analysis showed that overexpression of MEG8 and miR-770-5p resulted in increased cell apoptotic rate under glucose treatment. In addition, combined overexpression of MEG8 and miR-770-5p showed stronger effects.Conclusion: MEG8 may upregulate miR-770-5p through methylation to promote DN by promoting cell apoptosis.Keywords: diabetic nephropathy, MEG8, miR-770-5p, apoptosis